Multimodal Evidence of Atypical Processing of Eye Gaze and Facial Emotion in Children With Autistic Traits - Bagherzadeh-Azbari, Shadi; Lau, Gilbert Ka Bo; Ouyang, Guang; Zhou, Changsong; Hildebrandt, Andrea; Sommer, Werner; Lui, Ming (Frontiers in Human Neuroscience, 2022)
According to the shared signal hypothesis the impact of facial expressions on emotion processing partially depends on whether the gaze is directed towards or away from the observer. In autism spectrum disorder (ASD) several aspects of face processing have been found to be atypical, including attention to eye gaze and the identification of emotional expressions. However, there is little research on how gaze direction affects emotional expression processing in typically developing (TD) individuals and in those with ASD. This question is investigated here in two multimodal experiments. Experiment 1 required processing eye gaze direction while faces differed in emotional expression. Forty-seven children (9-12 years) participated. Their Autism Diagnostic Observation Schedule (ADOS) scores ranged from 0 to 6. Event Related Potentials (ERPs) were sensitive to gaze direction and emotion, but emotion processing did not depend on gaze direction. However, for angry faces the gaze direction effect on the N170 amplitude, as typically observed in TD individuals, diminished with increasing ADOS score. For neutral expressions this correlation was not significant. Experiment 2 required explicit emotion classifications in a facial emotion composite task while eye gaze was manipulated incidentally. A group of 22 children with ASD was compared to a propensity score-matched group of TD children (M = 13 years). The same comparison was carried out for a subgroup of nine children with ASD who were less trained in social cognition, according to clinician’s report. The ASD group performed worse in emotion recognition than the TD group, independent of emotion or gaze direction. However, for disgust expressions, eye tracking data revealed that TD children fixated longer on the eyes of the stimulus face with a direct gaze as compared with averted gaze. In children with ASD we observed no such modulation of fixation behavior as a function of gaze direction. Overall, the present findings confirm the hypothesis of an impaired sensitivity to gaze direction in children with ASD or elevated autistic traits, at least for specific emotions. Therefore, multimodal investigations of the interaction between emotional processing and stimulus gaze direction may provide markers for differentiating individuals along the autism trait dimension.